Sistem Pakar Untuk Perlindungan Tanaman Padi Dari Hama Dan Penyakit - Rachmat; Muhammad Roman Maulidin (Journal Teknik Dan Teknologi, 2024)
Public understanding of skin diseases in cattle is still low. Many people still rely on manual expertise from experts. So the costs borne by the community are quite expensive and in terms of time it is also less efficient. This consultation media is an application of a computer-based Expert System that uses facts and reasoning techniques to solve problems that usually can only be solved by an expert in a particular field. Expert systems provide added value to technology to help in dealing with an increasingly sophisticated information era. This Expert System application produces output in the form ofan application program or tool that can be used to diagnose possible skin diseases in cattle based on the symptoms input by the user. This system also displays the level of confidence of these symptoms in skin diseases entered by the user. The magnitude of the trust value is the result of calculations using the probability method. System testing shows that the system is able to diagnose cowhide disease based on the symptoms suffered by the patient even though these symptoms contain uncertainty. The diagnosis results are accompanied by a Certainty Factor value which shows the level of truth and accuracy of possible skin diseases in cattle.